2021
DOI: 10.2196/25793
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extensive Video Gaming and Cognitive Function Changes in Brain-Imaging Studies of Pro Gamers and Individuals With Gaming Disorder: Systematic Literature Review

Abstract: Background The World Health Organization announced the inclusion of gaming disorder (GD) in the International Classification of Diseases, 11th Revision, despite some concerns. However, video gaming has been associated with the enhancement of cognitive function. Moreover, despite comparable extensive video gaming, pro gamers have not shown any of the negative symptoms that individuals with GD have reported. It is important to understand the association between extensive video gaming and alterations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…To find these studies, we used the search terms multitasking / gaming and brain / MRI (MRI refers to magnetic resonance imaging, the most common brain-imaging method) at https://scholar.google.com and then ensured that the studied participants were healthy adolescents or young adults. For example, we excluded studies on individuals with signs of a gaming disorder (for a review of those, see Choi et al, 2021), except for one study (Zhou et al, 2019) that also reports separate results on the effects of gaming in participants with no such problems. In addition, we review findings from research without brain imaging on associations of media multitasking or gaming with cognitive functions.…”
mentioning
confidence: 99%
“…To find these studies, we used the search terms multitasking / gaming and brain / MRI (MRI refers to magnetic resonance imaging, the most common brain-imaging method) at https://scholar.google.com and then ensured that the studied participants were healthy adolescents or young adults. For example, we excluded studies on individuals with signs of a gaming disorder (for a review of those, see Choi et al, 2021), except for one study (Zhou et al, 2019) that also reports separate results on the effects of gaming in participants with no such problems. In addition, we review findings from research without brain imaging on associations of media multitasking or gaming with cognitive functions.…”
mentioning
confidence: 99%
“… 15 , 35 Six included some description of gaming in the main text. 10 , 15 , 39 , 46 , 47 , 50 These articles referred to e-sports (two articles), 34 , 39 multiplayer online games (one article), 15 AR games (one article), 15 video and/or computer games (five articles), 10 , 15 , 34 , 46 , 50 freemium games (one article), 10 and games that involved microtransactions (one article). 10 One article mentioned that it excluded studies that are exclusively on offline gaming.…”
Section: Has “Gaming” Been Defined In Peer-reviewed Publications?mentioning
confidence: 99%
“…Future research based on longitudinal data can provide information on players and their well-being at different points in time, shedding light on microlevel changes in this relationship. Further, this study does not address cognitive or behavioral consequences of video game play [43]. Lastly, the study relies upon voluntary, self-reported data, which is subject to limitations related to honesty, introspective ability, and sampling (or self-selection) bias.…”
Section: Limitations and Future Researchmentioning
confidence: 99%